A paradigm of comparative lexicology - Floriana Popescu (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2019)
Intended to bridge the gap between two languages of the Indo-European family, this is the first comprehensive bifocal approach to lexicological aspects. Through its theoretical distinctions and applications, the book recommends itself to language professionals and to any reader interested in learning more about words. It starts with a brief theoretical account of overlapping terms, which are given crystal-clear disambiguations. The book then focuses on structural representations of word formations and word relationships, outlining their hierarchicalness and branching directions and revealing various levels of materialization entailed by lexical productivity and frequency of occurrence. Each of these hierarchies defines its related techniques and explains lexical creations, adaptations or adoptions and interrelationships. The approach adopted here proves English to be consistent with formative and sense-related hierarchies, and shows it to have reached a climax in language evolution with its status of a global language, making it the standard in comparative linguistics.
Keywords: Lexicology